Pharmacotherapeutical approaches to decreasing hematocrit and increasing claudication distance in diabetic patients with peripheral vascular disease - Ürge, Jan; Strojil, Jan; Utíkal, Petr (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2005)
The paper deals with pharmacotherapeutical approaches to decreasing hematocrit in order to improve macro and microcirculation in arteries of lower limbs of type 2 diabetes patients. The study included 37 patients with diabetic angiopathy, all of whom had inoperable changes to arteries. In order to decrease hematocrit and cause haemodilution, we used 10 % solution of hydroxyethyl starch. Indications for inclusion in the study were carried out in close cooperation with a vascular surgeon. We applied hydroxyethyl starch according to a predetermined scheme. Using normovolemic and hypervolemic haemodilution, we decreased hematocrit to 0.41-0.42. Patients underwent a treadmill examination at the beginning of the study and then repeatedly during the course of study, when we measured the claudication distance to quantify, the effects of decreased hematocrit. The results show that the effect is most pronounced after 6 weeks, when hematocrit fell from a baseline of 0.435 to 0.421 (p < 0.01) and claudication distance increased to 51% (also significant). On average the claudication distance rose from 55.7 m to 84.6 m (p < 0.01). In the following weeks (after the sixth week of the study), the studied parameters changed only insignificantly (p > 0.05).
Keywords: Plasma Substitutes; intermitentní klaudikace; náhražky plazmy; Hematocrit; tolerance zátěže; deriváty hydroxyethylového škrobu; Middle Aged; mužské pohlaví; Walking; Hydroxyethyl Starch Derivatives; ženské pohlaví; chůze; Humans; Hemodilution; hemodiluce; Intermittent Claudication; lidé středního věku; hematokrit; Diabetic Angiopathies; diabetické angiopatie; Female; Exercise Tolerance; lidé; Male